Acervo Artístico da UFSM: reconectando memórias das artes visuais no ambiente virtual - Jesus, Flávia Queiroz Pereira de (2024)
The present research on memories of the UFSM Artistic Collection in the virtual environment, carried out in History, Theory and Criticism of Art (HTC) with an emphasis on Art Technology, aims to verify part of the history of the UFSM Artistic Heritage, and through the archives from the II Cabo Frio Biennial (1986) and eight works from the Collection, share some memories in the online virtual environment. The motivation is to provide the local community with another possibility to connect and think critically about the historical material present in the UFSM Artistic Collection. The methodology is qualitative, aligned with the postmodern thinking of Hans Belting, who perceives the existence of distinct narratives/contexts in Contemporary Art and the media, analyzing how these two areas converge or diverge. Field research is carried out through interviews with UFSM employees, and the university's physical and digital archives, conducting the study for different periods in the timeline of the University's Artistic Collection. Bibliographic research involves historians, curators and artists such as Giselle Beiguelman, Priscila Arantes, Pierre Lévy, Letícia Julião, Rudolf Frieling, Miguel Ferreira, Douglas Crimp and organizations such as Ibram, Iphan, ICOM and UNESCO, seeking to understand possible interrelations between Contemporary Art, curation, heritage and virtual environment. By combining the learning of field and bibliographical research, with laboratory research, the online exhibition with some works from the Artistic Collection, the creative experience of curation and expography in the online environment, the dissertation contributes to proposing a reconnection of the public with works of Art from UFSM.